An integrative review of the use of the concept of reassurance in clinical practice. Issue 3 (11th March 2022) - Akyirem, Samuel; Salifu, Yakubu; Bayuo, Jonathan; Duodu, Precious Adade; Bossman, Irene Fosuhemaa; Abboah‐Offei, Mary
Abstract: Aim: To synthesize evidence on the concept of reassurance in nursing practice. Design: Integrative review. Review Method: PubMed, OVID MEDLINE, CINAHL and PsycINFO were searched from their inception to the 30 May 2020. The search results were screened. We assessed the quality of primary studies using the Mixed Method Appraisal Tool. Included studies were analysed using narrative synthesis. The review protocol was pre‐registered (PROSPERO‐CRD42020186962). Results: Thirty‐two papers out of the 2, 771 search results met our inclusion criteria. The synthesis of evidence generated three intricate themes, namely "antecedents of reassurance, " "defining attributes of reassurance" and "outcomes of reassurance." Emotional distress was the main antecedent of reassurance. The three sub‐themes identified under defining attributes of reassurance include self‐awareness, emotional connectedness and verbal and non‐verbal techniques. Ultimately, reposing the confidence of patients and their families in healthcare professionals and the care delivery process to enable them to overcome their challenges constitutes the outcomes of reassurance.